Plasma Sphingolipid Profile Associated With Subclinical Atherosclerosis and Clinical Disease Markers of Systemic Lupus Erythematosus: Potential Predictive Value - Hammad, Samar M.; Harden, Olivia C.; Wilson, Dulaney A.; Twal, Waleed O.; Nietert, Paul J.; Oates, Jim C. (Frontiers in Immunology, 2021)
Systemic lupus erythematosus (SLE) is a chronic autoimmune disease that affects females more than males, with African Americans developing more severe manifestation of the disease. SLE patients are at increased risk for cardiovascular disease (CVD), and SLE women 35-44 years old have 50 fold the incidence rate of CVD. Because SLE patients do not follow the typical age and gender pattern for CVD, but instead an accelerated disease course, the traditional biomarkers of elevated LDL and total cholesterol levels do not accurately assess their CVD risk. Recently, we have reported that African American SLE patients had higher ceramide, hexosylceramide, sphingosine and dihydrosphingosine 1-phosphate levels compared to their healthy controls, and those with atherosclerosis had higher sphingomyelin and sphingoid bases levels than those without (PLoS One. 2019; e0224496). In the current study, we sought to identify sphingolipid species that correlate with and pose the potential to predict atherosclerosis severity in African American SLE patients. Plasma samples from a group of African American predominantly female SLE patients with well-defined carotid atherosclerotic plaque burden were analyzed for sphingolipidomics using targeted mass spectroscopy. The data demonstrated that at baseline, plaque area and C3 values correlated inversely with most lactoceramide species. After one-year follow-up visit, values of the change of plaque area correlated positively with the lactoceramide species. There was no correlation between LDL-C concentrations and lactoceramide species. Taken together, lactocylcermide levels may have a ‘protective’ value and sphingolipidomics have an added benefit to currently available tools in early diagnosis and prognosis of African American SLE patients with CVD.